SPOUSAL RIGHTS ON THE CLAIM OF FUTURE ASSETS AND FINANCIAL RESOURCES AS MATRIMONIAL ASSETS: A COMPARATIVE STUDY ON MALAYSIA’S LAW REFORM (MARRIAGE AND DIVORCE) ACT 1976, AUSTRALIA’S FAMILY LAW ACT 1975 AND NEW ZEALAND’S PROPERTY RELATIONSHIP ACT 1976. (International Seminar on Syariah and Law (INSLA), 2020)
Under section 76 of the Law Reform (Marriage and Divorce) Act 1976, the courts have limited classification of the matrimonial assets distributed upon divorce on the claim related to the existing assets acquired during the course of marriage such as matrimonial home, buildings, land, and etc. Nevertheless, with the economic status of the spouse, this traditional claim should be expanded to included claims on future assets such as EPF, Insurance, capital investments, and etc as distribution for matrimonial assets as some countries recognised on it.On this basis, most of the spouse has contributed either directly or indirect towards raising up the welfare of the family, thus upon divorce mostly non-acquired spouse left behind with nothing. Therefore, it is fair to include these future assets in distribution for matrimonial assets after a divorce. This paper intends to look into judicial decision approaches applied in the foreign countries such as New Zealand and Australia in determining financial resource otherthan the existing assets to overcome the economic disparity between spouse in matrimonial assets claim cases. This also discusses the legal principle which the Malaysian civil court could apply when it comes to claims on economic disparity to consider thefuture assets to be distributed as matrimonial assets. Research methodology adopted in this paper are judicialand doctrinal analysis. Undoubtedly, this would prevent the disadvantages economic disparity between spouse upon divorce by taking into consideration other elements such as future assets to be distributed as matrimonial assets.